Producing and Transgressing the Family: Intimate Technologies, State Surveillance, and China’s Uyghurs - Wozniak, Audrey (Lidé města, 2021)
In China’s Xinjiang Province, narratives of counterterrorism and economic development have accompanied heightened regional and national securitization, including the detainment in “re-education camps” of over one million Uyghurs and other ethnic minorities. Government language policies, technological surveillance, mass detentions, and homestay programmes intended to discipline Uyghurs into ideal political subjects enforce and transgress boundaries between the public and domestic spheres. These strategies of banal masked coercion reinforce norms of kinship and privacy while simultaneously enacting violent transgressive control over the subjects those norms produce. In this paper, I introduce the concept of “surveillance of intimate technologies” to convey how such surveillance strategies afford the creation and maintenance of the kinship relations they simultaneously betray. Intimate technologies such as smartphones become sites of sustaining both social ties and surveillance. Surveillance of intimate technologies also takes the form of government homestay campaigns to enlist over one million representatives of the Chinese state to enter Uyghur homes, act as “relatives”, and monitor Uyghurs for demonstrations of apparent extremism and subversion. I assert that surveillance of intimate technologies perpetuates fantasies of a private, removed, family space while also destabilizing its logics. These apparent perversions of kinship and family structures at once affirm their “valid” and normative modalities and also maintain the state’s appearance as a cohesive actor through demonstration of its reach into a constructed domestic domain.